Latino Language and Literacy in Ethnolinguistic Chicago. - Farr, Marcia (Lawrence Erlbaum Associates, 2005)
This volume--along with its companion Ethnolinguistic Chicago: Language and Literacy in the City's Neighborhoods--fills an important gap in research on Chicago and, more generally, on language use in globalized metropolitan areas. Often cited as a quintessential American city, Chicago is, and always has been, a city of immigrants.